Penentuan Taksiran Ketidakpastian (Uncertainty) dengan Metode Top-down dan Korelasinya Terhadap Total Error (TE) pada Parameter Hematologi - Salvia Maharani, Farah; Ridwanna, Surya; Harianto, Harianto; Rinaldi, Sonny Feisal (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2024)
Background: Uncertainty Measurement (UM) is defined as a parameter associated with a measurement result that characterizes a dispersion of values that can reasonably be associated with a quantity. ISO 15189 clause 5.5.1.4. states that the laboratory shall determine measurement uncertainty for each measurement procedure in the examination phase used to report measured quantity values on patients samples. Objectives: According to Westgard, there is debate about difference between the concepts of Uncertainty and Total Error (TE) so this study was conducted which aims to determine the uncertainty value of hematological parameters and determine the correlation of Uncertainty and TE. Materials and Methods: The material in this research are data of Internal Quality Control (IQC), External Quality Control (EQC), and Uncertainty data from the Sysmex XN-1000 calibrator. Results: Through the results the average uncertainty value of Sysmex XN-1000 2022 for leukocyte with low, medium and high levels, are ±19.05%, ±18.07 %, and ±15.94%, while for erythrocyte are ±4.46%, 4.10%, 4.16%, for hemoglobin are ±5.63, ±5.07, ±5.01, for hematocrit are ±8.99%, ±8.19%, ±8.19%, and for platelet are ±79.23%, ±62.23%, ±58.29%. Conclusions: Based on the uncertainty and TE calculated permonth for each lot number during 2022, the correlation was obtained between the Uncertainty and TE among leukocyte and hematocrit were stated to have a weak correlation, for hemoglobin and platelet it was stated quite correlated and erythrocytes are stated to be strongly correlated.